Molecular orientation of nickel phthalocyanine doped nematic liquid crystal composite under magnetic field - Ozdemir, Zeynep Guven; Canli, Nimet Yilmaz; Kilic, Mehmet; Koysal, Oguz; Yilmaz, Omer; Okutan, Mustafa (TAYLOR & FRANCIS LTD, 2016)
The electrical and dielectric properties of the nematic liquid crystal (E63) and Nickel Phthalocyanine (NiPc) doped E63 composite have been investigated by dielectric spectroscopy under 0-0.4T magnetic field. It has been observed that NiPc doping and external magnetic field, B decrease threshold voltage. Moreover, conductivity of the composite has an increasing tendency with magnetic field. Furthermore, a significant decrease in relaxation frequency with B has been interpreted as the simplification of molecular orientation. Hence, NiPc doping enhances the magnetic sensitivity of E63 and increases molecular orientation ability and conductivity.
Keywords: Liquid crystal; Nickel phthalocyanine; dielectric properties; magnetic sensitivity; molecular orientation; FREQUENCY-DEPENDENT CONDUCTIVITY; DIELECTRIC-RELAXATION; HELICAL POLYACETYLENE; CARBON NANOTUBES; AC-CONDUCTIVITY; STACKING; Chemistry; Crystallography; Materials Science